MANIFESTAÇÃO NEUROLÓGICA NA SÍNDROME HIPEREOSINOFÍLICA IDIOPÁTICA: RELATO DE CASO - Rodrigo de Souza Castro; Thiago Oliveira Chaves; Gabriela de Souza Castro; Flávia Junqueira Protázio (UniEVANGÉLICA, 2015)
Objective: To report a case of idiopathic hypereosinophilic syndrome manifested primarily with neurological manifestations and important response to corticosteroid therapy. Case description: A male patient, 47 years old, sought medical care due "tingling and weakness in the hands and legs for 6 months." He was admitted to the neurology sector. Six months before the admission in the hospital he had a paresthesia like tingling and burning associated with paresis in left leg that did not stop his walk. On last month presented with increased of paresis including right leg, worsening the gait. After two months the treatment with corticosteroids showed improvement of symptoms, at this time the patient use a walking stick to walk better. Comments: The early diagnosis associated with appropriate therapy improves prognosis of the patient and some patients have cure of the disease.